Penerapan Strategi Pembelajaran Kooperatif Tipe Think Pair and Share Untuk Meningkatkan Hasil Belajar Mata Pelajaran TEMATIK siswa kelas IV Di MI Darussalam Pikatan Wonodadi Blitar Tahun Ajaran 2019/2020 - Khoiruzzaim Kurniawan (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
Tematik lessons require a real understanding of various situations in the surrounding environment or society. For teachers, understanding the nature of Tematik certainly has a major contribution to make the Tematic learning process more meaningful. Seeing the presentation of the problems that occurred at MI Darussalam Pikatan, for this reason the researchers tried to conduct a classroom action research entitled